ANALISIS KEBIJAKAN PENDIDIKAN TENTANG PENDIDIKAN ANTI KEKERASAN - RESKI MULIANA; INDRA AYU LESTARI; JUANGSA JUANGSA (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
The background of this research starts from the many acts of violence that occur in the world of education, especially in schools. Education which is supposed to be a place to instill good character and character is actually a place for mushrooming of violence. Anti-violence education is one alternative that can be used to minimize the existence of violence in the world of education. The main purpose of this research is to find out the causes of violence in education and how to overcome it. Data collection is done by using interviews, documentation, and observation. Data analysis techniques use qualitative descriptive. The results showed that (1) violence occurs due to an environment that is not conducive, causing depression, severe stress so that there is a tendency to take action uncontrollably and can commit violence against others and yourself. (2) The way to overcome is anti-education violence instilled anti-violence values early on is one alternative solution to anticipate the occurrence of violence and create an educational unit environment that is free of violence.